Fatty Acid Profile of Microalgae Harvestingvia Immobilized Cell - N. H., Rushan; Nur Hidayah, Mat Yasin; N. R., Abu Sepian; N. I., Shafei; Farhan, Mohd Said (2018)
Microalgae are a group of microorganism that live in aquatic ecosystems. Microalgae are known as the alternative source of biodiesel production that can produce biomass, lipid, hydrocarbon and other complexed oil due to their simple unicellular structure and high photosynthetic efficiency. Microalgae have a lot of function and widely use in industries such as in health food, cosmetics nutrition, pharmaceutical industry and fuel production [1,2,3,4]. Harvesting of microalgae for biodiesel production has been a major challenge in the industry. The important process of harvesting microalgae for biodiesel production involves cultivation, harvestingand lipid extraction[5]. Microalgae harvesting is the process of separating the microalgae biomass from water.Immobilization microalgae cultivation is one of the current techniques in biotechnology. Sodium alginate is one of the preferably used matrix in immobilize technique because of its low toxicity and high transparency. The use of sodium alginate is to limit the freedom of microalgae movement [6].